Improved time domain diffraction analysis for SAW transducers of arbitrary shape - Jungwirth, Mario; Greifeneder, Thomas; Scheiblhofer, Klaus; Stoegmueller, A.; Weigel, Robert; Malocha, Donald; Ruile, Werner; Ruppel, Clemens (IEEE Ultrasonics Symposium, 1999)
A time domain (TD) diffraction analysis for SAW transducers was previously developed based on Huygen's principle. The analysis was performed using an approximation to the scalar two dimensional impulse response of an ideal point source which allowed for fast computation of diffraction effects in the time domain. A more rigorous derivation of the TD impulse response from the frequency domain (FD) angular spectrum of waves (ASoW) approach for the case of isotropic phase velocity has also been previously presented, and the extension of the analysis to include the velocity and electromechanical coupling anisotropy found in typical SAW substrates was also included. In order to be able to use the FFT for fast computation an equidistant sampling in the time domain must be evaluated. The present paper will report on an improved resampling-algorithm with a particular weighting to obtain the required equidistant impulses in the time-response, to be able to use the Fast Fourier Transform. Arbitrary transducer geometries can be dealt with by our TD technique. Numerical simulation results (impulse and frequency responses) for specific geometries will be presented
elib2cris::1512001600,jungwirth1999a